Create not to Commercialize: On the Everyday Practices of Russian Technopreneurs - Lebedeva, Daria (Journal of Economic Sociology, 2021)
What is the reason for the low commercialization of high-tech innovations in Russia? Given the Russian engineers’ high scores on initiative, creativity, and technical competence, why is there no successful launch of manufactured—often amazing—inventions on domestic and international markets? Does Russia have a specific way of development in the sphere of high technologies? The research team of sociologists from the European University at St. Petersburg (EUSP)—Olga Bychkova, Boris Gladarev, Oleg Harkhordin, and Zhanna Tsinman—offer answers to these questions in their book, Sci-Fi Worlds of Russian Hi-Tech. Based on a large set of in-depth interviews with entrepreneurs from Russia, as well as Finland, Taiwan, and South Korea, the authors’ focus is not on institutions but on the technopreneurs themselves, who update the hightech markets on their daily practices, ways of social interaction, worldviews, interactions with developers, technical prototypes, and themselves. Employing the concepts from the theory of practice and science and technology studies (STS), the authors have attempted to re-examine the life worlds of Russian technopreneurs and to align their individual narratives with the sociocultural context in which the daily life of developers is embedded. The researchers show the way that engineers live, in which value categories make sense of their work and daily practices, and how it may determine the technological development of the Russian economy and the whole society at the macro level. The book is filled with detailed and thorough descriptions of methodology and fieldwork, rich and illustrative quotations from the narratives of innovators, and the justification for the theoretical framework of the study. It is addressed to a wide readership and will be useful for sociologists, including those interested in research on science and technology, and for the general public who strives to open up the daily life of those whose works try to “crack the laws of the universe.”